Profile of Corneal Ulcer in a Month of harvesting Season in a Tertiary Level Eye Hospital of Eastern Nepal - Gautam, Vijay; Chaudhary, Abinash; Singh, Sanjay Kumar; Rai, Pooja Gautam (Nepalese Journal of Ophthalmology, 2018)
Introduction: Agricultural workers are prone to corneal injuries due to vegetative trauma especially during the harvesting season. This study reports the number of new cases of corneal injuries and corneal ulcer presenting in a month of harvesting season. Methods: This is a cross-sectional, hospital based study of all new cases of corneal injury and corneal ulcer presenting to the cornea department from 1st November, 2016 to 30th November, 2016. Typical or suspected cases of corneal ulcer of viral, immunologic or metabolic causes were excluded. Detailed history and clinical examination was carried out. Corneal scrapes in cases with corneal ulcer were taken and subjected to direct microscopy. Details of the findings were recorded in a proforma designed for the study. Statistical analysis was done by SPSS 18. Results: 259 cases presented during that period. Females were more affected (54%). Fifty-one percent of the cases presented from Nepal. Forty-eight percent gave history of ocular trauma by vegetative material. 40% presented within a week of development of symptoms, and about 40% after 2 weeks. Fifty percent of the cases had not presented to an eye care professional. 9% were using topical steroids. Progressive status of the disease was noted in 80%. Sixty-five percent presented with corneal ulcer of less than 2 mm size. Direct smear examination was carried out in 105 cases and 73% of them showed fungal elements. Conclusion: Awareness of agriculture related corneal injuries due to trauma by vegetative materials and methods to prevent such injuries is very important.